COMMUNITY EMPOWERMENT IN PRIVIDING MEASLES IMMUNIZATION TO INFANTS AT POSKESDES GAMPONG LAM ASAN, JAYA SUBDISTRICT, ACEH JAYA REGENCY - Ramadhan, Fitra; Arlianti, Nopa; Ahmad, Anwar (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Measles immunization coverage in Gampong Lam Asan remains below the national target of 95%, with coverage at 77.6% in 2017 and 63.2% in 2018. This study aims to assess the relationship between community empowerment and the implementation of measles immunization for infants. Method: This was a descriptive-analytic study with a cross-sectional design. The sample consisted of 53 respondents using a total population technique. Data were collected through observation, interviews, and documentation. Data were analyzed using univariate and bivariate methods with the chi-square test. Result: The study showed that 47.2% of infants had received measles immunization. The roles of health cadres, health workers, and PKK (Family Welfare Movement) were still at low activity levels. Bivariate analysis showed significant relationships between the role of health cadres (p-value=0.036), health workers (p-value=0.001), community leaders (p-value=0.004), and PKK (p-value=0.008) with measles immunization. Recommendation: The head of the health center should increase the involvement of health cadres and PKK in community education to support measles immunization coverage.